Digitalisasi Keuangan UMKM Berbasis Point of Sale: Implementasi Aplikasi ESB POS pada the Houseplants Coffee (Lembaga Pengembangan Kinerja Dosen, 2026)
This community service program aimed to implement the ESB Point of Sales (POS) application as a tool for financial digitalization at The Houseplants Coffee, an MSME located on Bengawan Street No. 16, Bandung City. The main problems faced by the partner included manual transaction recording, limited sales information, and weak control over inventory and cash flow. A Participatory Action Research approach was applied by involving the owner and staff in all stages of the program, including problem identification, planning, implementation, mentoring, and evaluation. The results indicate improved transaction recording accuracy, better inventory monitoring, and the availability of digital-based sales reports. The mentoring process also led to changes in work behavior, the establishment of new technology-based practices, and the emergence of a local leader supporting system sustainability. These findings demonstrate that integrating POS technology with a participatory approach effectively promotes sustainable digital transformation in MSMEs.